Rotation in Eucalyptus hybrid Plantations - Chaturvedi, A. N. (Indian Forester, 1973)
The paper studies relationships between MAI, Age, Basal Area and Top Height by the method of linear regression analysis. Loge (MAI) = -4.580245 - 0.996744 Loge (Age) + 0.628078 Loge (BA) + 2.466623 Loge (Top Height) has been selected to be the final regression equation. Tables basod on this relationship are given for varying top heights. It is indicated how the tables can be useful for determining spacing, rotations, yield class etc. Several other functions with regression analysis of each function is given.